Minimization of dispersive effects in the difference scheme telegraphic equations - Andros I.; Berzan V. (Problems of the Regional Energetics)
Paper deals with difference scheme for the system of telegraph equations, which describes the potential’s and current’s waves diffusion in a long line, considering Earth as the return line. Using the first differential approximation was obtained the approximation of the differential equations with the minimized influence of the dissipative and dispersing terms.